Radiation Therapy (IntechOpen, 2024)
As technology in radiation oncology moves forward, there is a need for continued process improvement in dose calibration and calculation of dose to tumor and normal tissue targets in a comprehensive and uniform manner. This is especially true for intensity modulation therapy, small-field radiation therapy with stereotactic techniques, brachytherapy, and protons. In this book, we examine modern topics in the evolving field of radiation dosimetry and close with a chapter on how modern dosimetry techniques will be applied to each oncology disease site.